Significance of Geographical Indications Laws in Nepal: A Comparative Study of Bhaktapur "Juju Dhau” and Greece "Greek Yogurt" - Sapkota, Laxmi (Kathmandu School of Law Review, 2022)
Juju Dhau (Yoghurt) is popularly known in Bhaktapur (Nepal) with its unique taste and quality. Regrettably it has not acquired global recognition yet. Apparently, Greek Yogurt, a similar type of Yogurt from Greece, enjoys international popularity. In this paper, the researcher conducted a survey alongside key informant interviews to reflect the perception and preference of Juju Dhau and comparatively analyzed the acquired data and information with Greek Yogurt. The result of the study reveals that the primary reason for producing Juju Dhau is its market access, good earning through creation of employment and consumer preferences on Juju Dhau. Additionally, the study reveals the perception of retailers is positive on Juju Dhau due to it being healthy, tasty and greatness in its flavor. The comparative study suggests about the risk of Greek Yogurt having the threat to become a genericide at a particular point of time. In this pretext, the Juju Dhau has to be promoted in international market but due diligence should be given while promoting it taking special reference form Greek experience. Furthermore, Juju Dhau is an intangible cultural heritage of Nepal. Nepal being a party to the Convention for the Safeguarding of the Intangible Cultural Heritage, it has binding obligation to safeguard Juju Dhau. The researcher, after comprehensive analysis of acquired data and information, identified the necessity of sui generis laws to be enacted merely for Juju Dhau. These laws will ultimately facilitate the recognition, protection, and promotion of Juju Dhau in Nepal and beyond.